Animal models of depression - T. L. Garibova; V. A. Kraineva; T. A. Voronina (LLC "Publisher OKI", 2017)
The review provides and describes in detail the main most commonly used behavioral experimental models of depression. Endophenotypes and criteria of validity of behavioral methods for evaluation of antidepressant activity in compounds are described. Modeling depression using laboratory animals allows us to understand the nature of depression in humans and to search for effective ways of treating.